OPPRESION AGAINST WOMEN IN NORTH COUNTRY MOVIE BY NIKI CARO: A MARXIST - FEMINIST APPROACH - SINTA, DITA MONILA (2011)
The major problem of this study is to elucidate the oppression against women reflected in North Country Movie by Niki Caro. The objectives of the study are; to analyse the structural elements of the movie and to analyse the major character of North Country Movie based on Marxist-Feminist perspective. In conducting this study, the researcher uses qualitative research in which the data are based on primary data from North Country Movie by Niki Caro. While secondary data are taken from references and materials related to study, whether by picking up from books and internet. Based on the structural analysis it is evident that in this movie, Niki Caro wants to deliver a message that women should fight against oppression and sexual harassment. First, structural approach is used to analyse the elements of the movie. It consists of characterization, setting, point of view, plot, style, theme, intent/ message, and cast. Meanwhile, technical elements involve mise-en-scene, cinematography, editing, and sound is analyzed to bring the readers understand totally. Second, based Marxist-Feminist analysis, it is clear that in this movie Niki Caro illustrates how women represent the oppression people in the society the Marxist-Feminist approach is used for analysing the oppression against women that influences her daily activity and behaviour toward life.